Combined Solar Simulator for Testing Photovoltaic Devices - Frolova, T. I.; Churyumov, G. I.; Vlasyuk, V. M.; Kostylyov, V. P. (My University, 2019)
The paper discusses a combined solar simulator, consisting of an electrodeless sulfur lamp with microwave excitation and a halogen lamp. It is shown that the emission spectrum of such a design of the combined solar simulator is closest to the spectral distribution of solar radiation in the wavelength range of 400 ... 1100 nm and has an increased service life compared to the solar simulator based on a xenon arc lamp. The spectral irradiance data of the solar simulator based on ASTM E927-10 in the wavelength range of 400 ... 700 nm have been measured. An excellent correspondence has been found between the observed results and existing spectral distribution of sunlight in the visible optical range at the level of AM 1.5G in according to standard ASTM G173-03.
Keywords: solar simulator; photovoltaic (PV) cells; microwave excitation; sulfur lamp; halogen lamp